2011
DOI: 10.3109/17453674.2011.574563
|View full text |Cite
|
Sign up to set email alerts
|

Radial shortening following a fracture of the proximal radius

Abstract: Background and purposeThe Essex-Lopresti lesion is thought to be rare, with a varying degree of disruption to forearm stability probable. We describe the range of radial shortening that occurs following a fracture of the proximal radius, as well as the short-term outcome in these patients.Patients and methodsOver an 18-month period, we prospectively assessed all patients with a radiographically confirmed proximal radial fracture. Patients noted to have ipsilateral wrist pain at initial presentation underwent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The only poor result was experienced by the patient who underwent a RH excision. Duckworth [ 25 ] retrospectively reviewed 60 patients affected by RH fracture, identifying 22 patients with radio-ulnar discrepancy. The good short term results (6 months) even after conservative management are to be considered non indicative, since usually patients experience a later worsening and no indication is reported about IOM assessment.…”
Section: Resultsmentioning
confidence: 99%
“…The only poor result was experienced by the patient who underwent a RH excision. Duckworth [ 25 ] retrospectively reviewed 60 patients affected by RH fracture, identifying 22 patients with radio-ulnar discrepancy. The good short term results (6 months) even after conservative management are to be considered non indicative, since usually patients experience a later worsening and no indication is reported about IOM assessment.…”
Section: Resultsmentioning
confidence: 99%
“…The interosseous membrane is an important stabilizer during axial loads on the forearm, and lesions are often not recognized. 20,21 Mason type I radial head fractures cause an intra-articular hematoma that limits the elbow range of motion (ROM). The elbow extension test uses this phenomenon to rule out intra-articular fractures of the elbow: an elbow that can be fully extended is unlikely to be fractured.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Nineteen of 22 patients had very favourable results. It was suggested that upwards of 30% of all persons with closed radial head fractures display evidence of an Essex‐Lopresti injury [17]. Their study highlights the need for clear definition of what constitutes a clinically important IOM injury because many individuals may have mild or partial injuries that go on to heal with minimal consequence [17,23].…”
Section: Detecting Longitudinal Instabilitymentioning
confidence: 99%